A Bibliometric Analysis of Risk Management and Sustainability in the Agri-Food Supply Chain: Future Directions - Dhita Morita Ikasari; Mokh Suef; Iwan Vanany (Engineering Proceedings)
Sustainability issues often trigger risks that require systematic management. Risks associated with various sustainability factors in the supply chain are becoming more pertinent in many food industries because of growing concerns about food safety and quality. This paper aims to identify the development of research topics related to risk management and sustainability in agri-food supply chains and to identify future research opportunities related to these topics through bibliometric analysis. We analyzed 320 articles from the Scopus database to determine publication trends, the most productive journals, the largest publishers, and the most cited articles. We visualized this bibliometric analysis using VosViewer version 1.6.20. The analysis reveals that “sustainability” is the most frequently studied keyword, clustering together with “risk management”, “agri-food supply chain”, “circular economy”, “supply chain resilience”, “artificial intelligence”, and “blockchain”, indicating a close relationship between these topics. “Food supply chain” and “agri-food supply chain” are also topics that have emerged in the last few years. However, there are still a few authors who publish on this topic. The combination of these keywords offers a potential avenue for future research.